Comparative detection of Giardia lamblia by immunochromatographic assay from stool samples in Erbil Province - Hataw Fryad Saber; Heshu J. Ahmed; Hawri M. Bakr (QALAAI ZANIST SCIENTIFIC JOURNAL, 2024)
Background: A flagellated protozoan parasite Giardia lamblia is one of the most significant causes of parasitic gastrointestinal illnesses. The main method of transmission is through the fecal-oral route, and the life cycle is straightforward and direct, including the motile trophozoite and nonmotile cyst stages. The aim of the study was to compare microscopy and immunochromatographic tests for diagnosing Giardia lamblia. Methods: This cross-sectional study was done by selecting 100 microscopically negative samples from groups of people In Erbil city, which were collected and stored at -20 °C for further testing. The result of the study conducted showed that, from 100 frozen samples, 3% were positive by immunochromatographic rapid testing. Males were more likely to participate in this study because most of the participants were food handlers. There was no statistically significant association between the gastrointestinal symptoms of positive patients; 1 (2.8%) has symptoms, and 2 (3.1%) are asymptomatic. It is concluded that Immunochromatographic assays are easy to perform, rapid, sensitive, and specific. It showed that the test may be useful in the diagnosis of infection in large cases or in studying the epidemiology of Giardia lamblia